Ethnic Disparity in the Incidence of Scoliosis Among Adolescents in Tianzhu Tibetan Autonomous County, China - Guo, Haibin; Chen, Nan; Yang, Yuqi; Zhou, Xuan; Li, Xin; Jiang, Yan; Huang, Jiaoling; Du, Qing (Frontiers in Public Health, 2022)
Abstract Objectives: To determine the influence of ethnic disparities, socioeconomic status and hukou on the incidence of scoliosis. Methods: We enrolled 2,445 junior high school students (Han: 1,153; ethnic minorities: 1,292) aged 12–16 years from two schools in Tianzhu Tibetan Autonomous County, Gansu Province from November 2020 to February 2021. We measured the angle of trunk rotation (ATR) using a scoliometer. Two-factor analysis of variance was used to comparatively analyze differences in the ATR according to ethnicity, age, sex, body mass index (BMI), and SES between the groups. Associations between risk factors and scoliosis were estimated using odds ratios and 95% confidence intervals with an unconditional multivariate logistic regression model for the two groups. Results: Adolescents with Han ethnicity were more likely to have scoliosis than their ethnic minority counterparts (10.8% vs. 7.1%, P<0.05). The ATR value in the Han group decreased with age whereas the minority group showed an upward trend (P<0.05). The difference between ethnic groups was not obvious, only at level 3. In particular, the ATR values among Han girls were significantly higher than those of ethnic minority girls(P<0.05). Compared with Han adolescents, the BMI of ethnic minorities had a greater impact on the ATR. A statistically significant difference in SES was found between the two ethnic groups (P<0.05). Hukou and parents’ occupation had an important influence on the onset of scoliosis. Conclusions: Han adolescents had higher ATR values and were more likely to have scoliosis than ethnic minority adolescents in our study. Growth and development indicators and differences in SES between the two groups played an important role.